Efgartigimod-associated Kaposi’s varicelliform eruption and herpetic conjunctivitis in a patient with seropositive ocular myasthenia gravis: a case report and review - Ge, Lingzhi; Li, Yanyan; Sun, Ying; Chen, Wenfang; Ni, Xiaoli; Wei, Fangli; Mu, Zhen (Frontiers in Immunology, 2024)
Background: Efgartigimod (Efgartigimod alpha fcab, Vyvgart™)is a pioneering neonatal Fc receptor (FcRn) antagonist for the treatment of severe autoimmune diseases mediated by pathogenic immunoglobulin G (IgG) autoantibodies, including myasthenia gravis (MG). It is a well-tolerated drug with minor side effects, such as headache and upper respiratory (lung) and urinary tract infections.Here, we present a case of Kaposi's varicelliform eruption (KVE) and herpetic conjunctivitis related to efgartigimod in a 60-year-old patient with ocular MG (OMG).A 60-year-old Chinese male suffered from acetylcholine receptor antibody positive (AChR Ab+) OMG for 8 years. During this period, he underwent first-line treatment treatment with systemic corticosteroids, cyclosporine, cyclophosphamide and so on, but had poor symptom improvement. On the recommendation of his attending neurologist, he received one cycle of intravenous efgartigimod (10mg/kg, once weekly for 4 weeks). The patient erupted with fever and widespread painful blisters and edema on the face the third day after his last intravenous infusion. And the patient also complained of increased secretions, foreign body sensation in both eyes. Laboratory tests confirmed infection with herpes simplex virus (HSV). A diagnosis of efgartigimod-associated KVE and herpetic conjunctivitis was made. After intravenous administration (5-10mg/kg, 3 times a day, every 8 hours) for 10 days, the patient was cured without residual complications.This case is the first report of the patient with KVE and herpetic conjunctivitis related to efgartigimod in PubMed. That is rare and unusual. Clinicians should be alert to the rare symptoms relate to efgartigimod.